2007
DOI: 10.1029/2006jd007436
|View full text |Cite
|
Sign up to set email alerts
|

Ozonolysis of α‐pinene at atmospherically relevant concentrations: Temperature dependence of aerosol mass fractions (yields)

Abstract: [1] Despite a number of smog chamber studies of the a-pinene/O 3 system, the effect of temperature on a-pinene secondary organic aerosol (SOA) mass fractions (or yields) remains poorly understood. In this study, the temperature dependence of secondary organic aerosol mass fractions (AMF) during ozonolysis of a-pinene is investigated in a temperature controlled smog chamber. Experiments were performed with and without ammonium sulfate aerosol seeds at RH < 10% and at 0°C, 15°C, 20°C, 30°C and 40°C. The initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
276
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(312 citation statements)
references
References 37 publications
36
276
0
Order By: Relevance
“…However, even after steady-state is reached, the particle counts decreased with increasing distance along the flow tube as expected from particle losses to the walls due to settling and coagulation. The wall loss constant, calculated in a manner similar to that of Pathak et al (2007) using data from P1 through P5 produced a value for k wall = 8.8 × 10 -5 s -1 . The measured particle counts at P2 FIG.…”
Section: A Co 2 Flow Studiesmentioning
confidence: 99%
“…However, even after steady-state is reached, the particle counts decreased with increasing distance along the flow tube as expected from particle losses to the walls due to settling and coagulation. The wall loss constant, calculated in a manner similar to that of Pathak et al (2007) using data from P1 through P5 produced a value for k wall = 8.8 × 10 -5 s -1 . The measured particle counts at P2 FIG.…”
Section: A Co 2 Flow Studiesmentioning
confidence: 99%
“…For the generation of biogenic SOA, a set of experiments utilizing the dark ozonolysis of α-pinene was conducted following the experimental conditions given by Pathak et al (2007), shown in Table 1. First, O 3 was introduced inside the chamber and then an injection of α-pinene initiated the production of SOA.…”
Section: Biogenic Soamentioning
confidence: 99%
“…Fry et al, 2009;Cai and Griffin, 2006;Griffin et al, 1999;Hoffmann et al, 1997), seed aerosol (e.g. Kroll et al, 2007;Pathak et al, 2007;Chan et al, 2007;Cocker et al, 2001), temperature (e.g. von Hessberg, et al, 2009;Saathoff et al, 2009;Pathak et al, 2007), relative humidity (RH) (e.g.…”
Section: Q Hao Et Al: Mass Yields Of Secondary Organic Aerosolsmentioning
confidence: 99%
“…Kroll et al, 2007;Pathak et al, 2007;Chan et al, 2007;Cocker et al, 2001), temperature (e.g. von Hessberg, et al, 2009;Saathoff et al, 2009;Pathak et al, 2007), relative humidity (RH) (e.g. von Hessberg, et al, 2009;Cocker et al, 2001;, UV intensity (e.g.…”
Section: Q Hao Et Al: Mass Yields Of Secondary Organic Aerosolsmentioning
confidence: 99%